2012
DOI: 10.1353/csd.2012.0026
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning Students Make as Participants in Short-Term Immersion Programs

Abstract: The purpose of this article is to present the results of a multi-site case study designed to investigate students’ experiences as participants in four week-long immersion programs (New York City, Peru, the Czech Republic, Chicago). Results highlight the significance of the context of the trips and specific characteristics of the trip (e.g., getting out of the bubble, boundary crossing, and personalizing), which served as the springboard for learning and meaning making. In particular, meaning making focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
99
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 27 publications
10
99
1
Order By: Relevance
“…Participants in general reported quite a lot of growth in this area and a fairly strong influence of their AB experience on this outcome. Consistent with prior research (e.g., Jones et al, 2012;Niehaus, 2012b), ABs can provide a context that facilitates the informal interactions with diverse others necessary for student development (Bowman, 2010(Bowman, , 2011Denson, 2009;Gurin et al, 2002).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Participants in general reported quite a lot of growth in this area and a fairly strong influence of their AB experience on this outcome. Consistent with prior research (e.g., Jones et al, 2012;Niehaus, 2012b), ABs can provide a context that facilitates the informal interactions with diverse others necessary for student development (Bowman, 2010(Bowman, , 2011Denson, 2009;Gurin et al, 2002).…”
Section: Discussionsupporting
confidence: 69%
“…The findings that there were no significant differences between White students and Students of Color and no differences between Students of Color who volunteered in racially similar and racially different communities, however, point to the possibility that what Students of Color may be learning about racial differences may be coming from another source than the community. As other research on service-learning and ABs has found, often students learn just as much, if not more, from the other student volunteers as they do from community members (e.g., Jones et al, 2012;Niehaus, 2012b). As most Students of Color were likely volunteering in student groups that were predominantly White (evidenced by the vast majority of respondents who were White), this may have been the source of their learning about racial differences.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, Jones, Rowan-Kenyon, Ireland, Niehaus, and Skendall (2012) found that students participating in short-term immersion programs (including ABs) deepened their understanding of social issues by connecting these issues to community members' lived experiences. Students were "able to put a name and a face" on the social issues about which they were learning, to compare "their own lives with the lives of the people they met" (p. 209), and to apply this knowledge to classroom conversations about social issues when they returned to campus.…”
Section: Contexts That Facilitate Integrative Learningmentioning
confidence: 99%
“…They also questioned the integrative potential of short-term experiences like ABs. Similarly, Jones et al (2012) found that despite the connections students made during their immersion experiences, many found it challenging to integrate what they had learned with their lives back on campus. This finding raises the important question of what types of experiences are most conducive to integrative learning.…”
Section: Contexts That Facilitate Integrative Learningmentioning
confidence: 99%